Tata Kelola Konten Digital pada Multimedia Center (MMC) Diskominfosantik Provinsi Kalimantan Tengah dalam Mendukung Komunikasi Publik dan Meningkatkan Kepercayaan Masyarakat - Selva Ayu Safitri; Yuliana Hellen; Noorjaya Nahan; Syayuti Syayuti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The development of information and communication technology encourages the government to use digital media as a means of public communication to convey information to the public quickly and openly. The Multimedia Center (MMC) of the Central Kalimantan Provincial Diskominfosantik plays a role in the management and dissemination of local government information through official websites and social media. This research aims to find out the governance of digital content in MMC in supporting public communication and increasing public trust. The research uses a qualitative approach with a descriptive method. Data were obtained through interviews, observations, documentation, and literature studies, then analyzed using the Miles and Huberman model. The results of the study show that digital content governance in MMC is carried out in a structured manner through the stages of planning, production, publication, evaluation, and content documentation. The use of digital media helps the government convey information quickly, informatively, and easily accessible to the public, thereby supporting public communication and increasing public trust in local governments.